(untitled) - Gammidge, Mick (Cambridge, 2004)
Speaking Extra is a photocopiable resource book designed for use with young adults (16+) and adults. It contains over 50 easy-to-prepare activities for elementary, intermediate and upper-intermediate level. The material offers teachers a refreshing approach to 18 familiar topics and can easily be used to supplement existing coursebooks. The activities will engage and motivate students as they practise speaking in realistic contexts. At the same time students will practise a range of speaking skills including negotiating, persuading,expressing opinion and requesting information. At the same time as practising a key listening skill, the activities integrate the other skill areas. Speaking Extra is accompanied by an optional CD to bring some of the activities to life.
Keywords: English language,English language,Speaking; Study and teaching,Textbooks for foreign speakers